Characteristics of classroom chairs and desks in use in senior secondary schools in Ibadan, Oyo State, Nigeria (2010)
The current status of wooden classroom chairs and desks in use in selected Secondary Schools (SS) in Ibadan was investigated. Fifty-four SS were randomly selected; 12 each from rural and semi-urban, and, 10 from urban areas of Ibadan. Random sampling survey was conducted using structured questionnaire and oral interview and to collect data on chairs and desks types, designs, construction materials and methods, durability and cost factors. Joint features, failure pattern and causes were evaluated via on-the-spot assessments. Simple descriptive statistical tool was used for data analyses. Similar furniture geometry, constructional method and failure mode were noted in rural, semi-urban and urban schools. About 90% of the Schools were using wooden chairs and desks. The two predominant designs were the Single-User (SU), and Multiple-User (MU) types. The production philosophy for both furniture types was one-size-fit all. The SU and MU chairs and desks had a relatively short service life with over 80% of them failing within three months. Poor jointing was responsible for over 69% of the failure. As at December, 2009 a pair of SU and MU chairs and desks cost N2500 and N3500 respectively.